Integration of Information and Communication Technology in Mathematics Teaching in Metro Manila Public Secondary Schools - Cajilig, Norma G. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 67 No 1 (2009), 2011)
This is an investigation on the adoption patterns of Metro Manila public secondary school teachers while information and communication technology (ICT) is being integrated into their teaching. Evidence shows that the majority of the teachers had highly favorable attitudes toward the use of new technologies in instruction. This disposition was brought about, among other things, by the influence of authority and/or the status individuals normally attach to technology innovation. This study further shows that while the enthusiasm level for integration was high, the extent of ICT implementation was poor mainly due to the lack of computer facilities and teacher training programs. It is recommended that the government take advantage of the teachers’ enthusiasm by providing the teachers with necessary tools and opportunities to improve their teaching.